PENGARUH PASIR, ABU TERBANG, DAN AIR PADA KARAKTERISTIK MEKANIS TANAH LEMPUNG - Soewignjo Agus Nugroho; Ferry Fatnanta; Syawal Satibi; Muhamad Yusa; Agus Ika Putra; Gunawan Wibisono (Matriks Teknik Sipil, 2025)
The shear strength and bearing capacity of soil are influenced by its type, mineral composition, and particle size. Both cohesion and the friction angle play significant roles in determining soil strength, while density is crucial for supporting forces. This study examines the effects of grain size, soil minerals, and water content on the shear strength and bearing capacity of soil. Various tests such as California Bearing Ratio, Direct Shear, and Unconfined Compression Test are conducted on sand and clay, compacted with different numbers of strikes and water contents. The study also explores the impact of organic soil and fly ash on shear strength. Additionally, immersion tests are performed to assess how water absorption affects the soil’s properties. Results show that compression at the optimum moisture content (OMC) produces the highest strength, while compression at higher moisture levels results in greater strength loss compared to drier conditions. At a constant water content, increased soil density leads to higher bearing capacity. Conversely, excess water content reduces the soil's strength. The presence of clay, fly ash, and organic material increases water absorption capacity. In sandy soils, the distribution of grain size significantly influences shear behavior. The addition of clay enhances both the friction angle and soil cohesion, while higher fly ash content tends to reduce the friction angle and improve soil cohesion. Interestingly, cohesion appears to be unaffected by the sand's gradation.  Keywords: bearing capacity, clay, fly ash, shear strength, sand.